Silicon-substituted calcium phosphate promotes osteogenic-angiogenic coupling by activating the TLR4/PI3K/AKT signaling axis. (September 2022) - Kong, Yuanhang; Zhang, Xin; Ma, Xinnan; Wu, Leilei; Chen, Dechun; Su, Bo; Liu, Daqian; Wang, Xintao
Silicon-substituted calcium phosphate (Si-CaP) is a promising bioactive material for bone tissue engineering. The mechanism of Si-CaP regulates osteogenic-angiogenic coupling during bone regeneration has not been fully elucidated. In this study, we screened the targets of Si-CaP and osteogenic-angiogenic coupling. 83 common genes were regarded as key targets for Si-CaP regulation of the osteogenic-angiogenic coupling. Then, we performed protein-protein interaction analysis, GO and KEGG enrichment analysis of these 83 targets to further predict their molecular mechanism. Our results showed that Si-CaP treatment could regulate the osteogenic-angiogenic coupling by up-regulating the expression of Toll-like receptor 4 (TLR4), and the phosphorylation of AKT which in turn activating the PI3K/AKT signaling pathway, promoting the expression of RUNX2, OPN, VEGF. In addition, we also found that TLR4 siRNA treatment could block the PI3K/AKT signaling pathway, while inhibiting the promoting effect of Si-CaP. However, although LY294002 can achieve the same inhibitory effect as TLR4 siRNA by blocking the PI3K/AKT signaling pathway, it could not affect the expression of TLR4. This indicates that TLR4 is an upstream activator of PI3K/AKT signaling pathway. These results are highly consistent with the prediction of bioinformatics. In conclusion, we have elucidated the role of TLR4/PI3K/AKT signaling axis in Si-CaP mediated osteogenic-angiogenic coupling for the first time. This study provides new data onto the regulatory role and molecular mechanism of Si-CaP in the process of osteogenic-angiogenic coupling, which strongly supports its wide application for bone tissue engineering.